Digital art in light of NFT: Market power and legal uncertainty - O. S. Kulakova (Цифровое право, 2022)
Digital art is the result of creative activity practiced in the virtual space. There is no unified concept of digital art in Russia, and there is no legislative consolidation of this term. In this regard, attempts to find an answer to what digital art is and what rights its acquirer has are topical issues of Russian legal science. At the same time, under the influence of technology, as a result of the development of the blockchain, new ways of handling digital art objects have appeared. The appearance of non-fungible tokens (NFT) causes a lot of legal problems. The study of these problems is the most important task for modern lawyers. The purpose of the study is to identify the legal qualification of digital art objects. In this regard, the author sets the task to study the structure of NFT as an object of civil law. The purpose of the article is also to identify potential risks for intellectual property rights holders when issuing NFT.The methodology of this research is based on the use of a set of general scientific methods and specific methods of analysis used in legal science: system-structural method, system-functional, induction and deduction, analogy, method of formal logic and system approach. In particular, the dialectical method provides an opportunity to systematically explore the unity of social content and legal form of art objects in the digital space. The formal legal method makes it possible to form legal categories by highlighting the main features of phenomena related to research questions.The author has made assumptions about the legal nature of digital art and NFT, as well as their place in the system of intellectual property law. The author has come to the conclusion that crypto art is one of the types of digital art. A specific feature of cryptographic art objects is that their emergence and existence is possible only in blockchain. As a result of the conducted research, it has been revealed that not all NFTs connected to art objects are crypto-art objects in digital commerce.